Metode Lagrange Interpolasi Polinomial: Analisis Komparatif Implementasi pada MATLAB dan Aplikasi Metode Numerik: Kalkulator - Hidayat, Ahmad Rafli; Aristika, Bella; Ari Wibowo (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Lagrange polynomial interpolation is used to estimate the value of a function based on discrete data points. This research aims to explore and compare the effectiveness of the lagrange polynomial interpolation method using two technological approaches, namely the MATLAB software and the Android-based application Numerical Methods: Calculator. This study uses a descriptive qualitative approach with a comparative method to test the efficiency, accuracy of results, ease of use, and visualization of both applications. The results show that MATLAB excels in computational capabilities and visualization, while the Numerical Method: Calculator application is more accessible and suitable for learning. This research contributes to the selection of learning aids and the solution of lagrange polynomial interpolation problems tailored to user needs and the complexity of the issues.